ANALISIS FAKTOR-FAKTOR PENGHAMBAT YANG BERPENGARUH TERHADAP WAKTU PROYEK IRIGASI DI PROVINSI ACEH - Anita Rauzana; Gunawan Gunawan; Masimin Masimin (JURNAL TEKNIK SIPIL, 2016)
Abstract:Delays in project implementation is an obstacle that is generally always detrimental to both owners and contractors. Based on the format of data to monitor the work packages Aceh Irrigation Department 2011 budget year were funded by the APBA, experienced delays in completion of the work in the field. This study aims to identify the factors and the dominant factors that cause occurred inhibiting the implementation of the irrigation project in the province of Aceh, as well as analyzing the shape of the relationship and influence between the inhibiting factors against time irrigation project in the province of Aceh. Projects reviewed is the irrigation project has been completed starting from the year 2012-2015, with funding from the APBA, which is aimed at contractors in irrigation. Factors that cause the occurrence of inhibiting the implementation of the irrigation project in the province of Aceh is caused by factors of labor, material factors, factors of design and planning, factor of implementation and labor relations, factors of equipment, factor conditions and circumstances on the ground, and factors beyond the ability of contractors , The dominant factor in the cause of inhibiting the implementation of irrigation projects in Aceh province is due to factors of labor, with a mean value of 4,328. Relations inhibiting factors against time irrigation project in the province of Aceh, which has a high correlation is a factor of equipment, factors and circumstances on the ground conditions, and factors beyond the ability of the contractor to the Pearson correlation coefficient between 0,700-0,900. Effect of inhibiting factors against time irrigation project in the province of Aceh, the most influential factor is the equipment, with a regression coefficient of 0,572.Keywords : Retarder, time, irrigation projectsAbstrak : Keterlambatan pelaksanaan proyek merupakan hambatan yang umumnya selalu merugikan pemilik maupun kontraktor. Berdasarkan data format pantau paket-paket pekerjaan Dinas Pengairan Aceh tahun anggaran 2011 yang bersumber darid ana APBA, mengalami keterlambatan dalam penyelesaian pekerjaan di lapangan. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor serta faktor dominan yang  menyebabkan terjadi penghambat pelaksanaan pada proyek irigasi di Provinsi Aceh, sertameng analisis bentuk hubungan dan pengaruh antara faktor-faktor penghambat terhadap waktu proyek irigasi di Provinsi Aceh. Proyek yang ditinjau adalah proyek irigasi yang telah selesai dilaksanakan mulai dari tahun 2012-2015, dengan sumber dana dari APBA, yang ditujukan pada kontraktor bidang irigasi. Faktor-faktor penyebab terjadinya penghambat pelaksanaan pada proyek irigasi di Provinsi Aceh adalah disebabkan oleh faktor tenaga kerja, faktor material, faktor desain dan perencanaan, faktor pelaksanaan dan hubungan kerja, faktor peralatan, faktor kondisi dan keadaan di lapangan, danf aktor di luar kemampuan kontraktor. Faktor dominan penyebab terjadinya penghambat pelaksanaan pada proyek irigasi di Provinsi Aceh adalah disebabkan faktor tenaga kerja, dengan nilai mean sebesar 4,328. Hubungan faktor-faktor penghambat terhadap waktu proyek irigasi di Provinsi Aceh, yang mempunyai hubungan tinggi adalah faktor peralatan, faktor kondisi  dan  keadaan di  lapangan, dan faktor di luar kemampuan kontraktor dengan nilai koefisien korelasi  Pearson antara 0,700-0,900. Pengaruh faktor-faktor penghambat terhadap waktu proyek irigasi di Provinsi Aceh, yang paling berpengaruh adalah faktor peralatan, dengan  nilai koefisien  regresi  sebesar  0,572.Kata kunci : Penghambat, waktu, proyek  irigasi